Effect of aluminium content on the tensile properties of Mg-Al-Zn Alloys - Abdul Latif, N.; Sajuri, Z.; Syarif, J. (Fakulti Kejuruteraan, 2014)
The aim of this study is to investigate the effect of aluminium content on microstructure, tensile properties and work hardenability of Mg-Al-Zn alloys. Two types of magnesium alloys were investigated i.e. AZ31 and AZ61, where the aluminium contents were 3% and 6%, respectively. Microstructure observation revealed that higher aluminium content decreases the grain size and increases the volume of Mg17Al12 precipitations. From the tensile test, AZ61 demonstrated higher yield stress and tensile strength while maintaining the elongation as compared to AZ31. The work hardening rate for AZ61 was also greater as compared to that of AZ31.